Students’ Perception in Creating Multimedia with Paci Model through TPACK Framework In English Department Mulawarman Universitas - Siti Hardiyanti Fatimah; Iwan Setiawan; Anjar Dwi Astuti (English Department, Faculty of Teacher Training and Education, Mulawarman University, 2018)
The purpose of the study is to know the students' perception in creating multimedia with PACI model through TPACK framework. This research was conducted in English Department of Mulawarman University. The design of this study was qualitative study that it is purposed to illustrate students’ perception about creating multimedia with PACI model through TPACK framework